Evaluasi Kesesuaian Lahan Untuk Beberapa Tanaman Pangan Dan Perkebunan Di Kecamatan Burau Kabupaten Luwu Timur Sulawesi Selatan - SURYAWAN, IDA BAGUS; ADI, I GUSTI PUTU RATNA; DIBIA, I NYOMAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.9, No.1, Januari 2020, 2020)
Evaluation Of Land Suitability For Several Food Crops And Plantations In Burau Sub-District, East Luwu Regency Of South Sulawesi This research aims to discover the actual and potential of land suitability, limited factor, improvement effort, land use management and the creation of land suitability maps and direction of use for some food crops and plantations. Plants that are evaluated include rice, corn, chili, pepper, cocoa, clove and oil palm. The research was conducted in Burau subdistrict from February 2019 to June 2019. Based on the result overlapped of soil type, land use, and slope were obtained seven homogeneous land units. The research methods used are surveys, analyses, and classification of land suitability based on the criteria of growing plant requirements that are matched with the characteristics/quality of land. Results show that classes of actual land suitability for some food crops and plantations are S1 (very appropriate) until N (not appropriate). The limited factors in the research area include: temperature, rainfall, drainage, texture, CEC soil, base saturation, pH, C-Organic, N-Total, P2O5, K2O, slope, and the erosion hazard. Improvement of the land-suitability class can be done with improvement effort except temperature and texture because they are permanent barrier factor. Potential suitability class of land for some food crops and plantations evaluated are S1 (highly appropriate) until S3 (marginal appropriate), with limited factors among others temperature, texture and slope factors. Land use recommendations on AISw, AIISw, AIKk, and AIKks are rice, corn and chili. AIIKks, PsIIIKk, and PsIVKks are recommended for pepper, cocoa, clove, and palm oil.